Everything on a waffle - Horvath, Polly (New York : Farrar Straus Giroux, 2001)
Eleven-year-old Primrose living in a small fishing village in British Columbia recounts her experiences and all that she learns about human nature and the unpredictability of life in the months after her parents are lost at sea.
Keywords: Self-reliance -- Fiction; Uncles -- Fiction; Parent and child -- Fiction; Foster home care -- Fiction; Interpersonal relations -- Fiction; British Columbia -- Fiction